Ultraearly Hematoma Growth in Acute Spontaneous Intracerebral Hemorrhage Predicts Early and Long-Term Poor Clinical Outcomes: A Prospective, Observational Cohort Study - Wang, Wen-Juan; Lu, Jing-Jing; Liu, Li-Ping; Jia, Jiao-Kun; Zhao, Xing-Quan (Frontiers in Neurology, 2021)
Aims — Although prognostic importance of ultraearly hematoma growth (uHG) in acute, non-traumatic intracerebral hemorrhage (ICH) has been established for early outcomes, longer-term clinical outcomes are lacking. We aimed to determine the association of ultraearly hematoma growth (uHG) with early and 1-year clinical outcomes after acute ICH in a larger and broader range of patients. Methods — We studied 589 patients with acute (< 6 hours) spontaneous ICH. uHG was defined as baseline ICH volume/onset-to-imaging time (ml/h). Multivariable logistic regression analyses were performed to determine the association of uHG with in-hospital mortality, 90-day and 1-year poor outcome (3 ≤ modified Rankin Scale) after ICH. Results — The median speed of uHG was 4.8 mL/h. uHG > 9.3 mL/h was independently related to in-hospital mortality (odds ratio [OR] 2.81, 95% confidence interval [CI] 1.52 - 5.23), 90-day poor outcome (OR 3.34, 95% CI 1.87 - 5.95) and 1-year poor outcome (OR 3.59, 95% CI 2.01 - 6.40) after ICH. The sensitivity of uHG > 9.3 mL/h in the prediction of in-hospital mortality, 90-day poor outcome and 1-year poor outcome is 68.8%, 48.0% and 51.1%, respectively. Conclusions — uHG was a useful predictor of in-hospital mortality, 90-day and 1-year poor outcome after acute ICH. The combination of both uHG and baseline ICH volume could allow better selection of ICH patients at high risk of poorest clinical outcomes for future clinical trials to improve early and long-term clinical outcome.